Session Topic: New Techniques for Asessing International Risk: Discussion - Aliber, Robert Z. (Journal of Finance, 1979)
Robert Z. Aliber, Session Topic: New Techniques for Asessing International Risk: Discussion, The Journal of Finance, Vol. 34, No. 2, Papers and Proceedings, Thirty-Seventh Annual Meeting, American Finance Association, Chicago, Illinois, August 29-31, 1978 (May, 1979), pp. 436-438